In-situ Construction of Superhydrophilic g-C3N4 Film by Vapor-Assisted Confined Deposition for Photocatalysis - Jia, Fuhao; Zhang, Yizhu; Hu, Wenjuan; Lv, Min; Jia, Changchao; Liu, Jian (Frontiers in Materials, 2019)
Herein, we report an improved strategy for the synthesis of superhydrophilic g-C3N4 film by vapor-assisted confined deposition method. With minimum amount of precursor, the vapor could be confined in the microenvironment for facilitating the film growth on both sides of the substrates. The obtained films showed similar physiochemical properties with the bulk counterpart and could be peeled off from the substrates by soaking in hot water. The free-standing film is flexible and superhydrophilic, featuring many microfibers atop. The g-C3N4 film from both sides of the substrates could be used in the photocatalytic dye degradation in a repeated manner and showed excellent performance and stability. The current work should shed light on the optimized growth of the g-C3N4 film and could find more application in future device field.